Characterization of calcium transporters during the pollen tube growth in Arabidopsis thaliana - García Bossi, Julián (2019)
In plants, calcium signals are involved in multiple physiologicalprocesses such as stomatal opening, stress responses, and polarized growth ofroot hairs and pollen tubes. These signals are given as repetitive oscillationsof cytosolic free Ca2+ where the intensity and amplitude correlateaccording to the stimulus. Pollen tube growth occurs through the concertedaction of different factors such as pH, ROS, actin and calcium gradient. Anyimbalance between these factors causes aborted pollen tubes and therefore, defectsin fertility.In this work, we propose to perform a functional study of the P2B typecalcium pumps (Autoinhibited Ca2+-ATPases,ACAs), in pollen tubes of Arabidopsis thaliana. These pumps are mainlylocated in vacuole, endoplasmic reticulum and/or plasma membrane and areinvolved in removing calcium from the cytoplasm. Studies conducted with ACAinsertional mutants have shown that these pumps have a role beyond themaintenance of Ca2+ homeostasis. Since some Arabidopsis ACAs arespecifically expressed in mature pollen, we propose to explore pollen-pistilinteractions of ACA mutant plants.  Wewill also study calcium dynamics during pollen tube growth. These results will provide new perspectivesabout how pollen tube growth is regulated and it will be also applicable toother cellular polar growth models.